PSYCHOLOGICAL FEATURES OF PERCEPTION OF CREATIVE ADVERTISING - O.Yu. Vodopyanova (Academy of Cognitive and Natural Sciences, 2022)
In the article the psychological features ofperception o f Creative advertising and primary factors o f Creative advertising as Creative process are uncovered.